2023
DOI: 10.1021/acsomega.3c00880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poultry Manure on the Growth, Physiology, Yield, and Yield-Related Traits of Maize Varieties

Abstract: Industries play a significant role in the improvement of lifestyle and in the development of a country. However, the byproducts from these industries are a source of environmental pollution. The proper use of the byproducts of these industries can help to cope with environmental pollution. Some byproducts have high nutritional content and are good for crop plants. The purpose of this research was to investigate the effect of different rates of poultry manure on the soil chemical properties, growth, and yield o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…Various research has established that water stress causes a decrease in growth, as seen by changes in plant growth parameters such as height, number of branches, and dry matter (Zubaer et al, 2007, Boutraa et al, 2010Talukdar, 2013). Poultry manure can overcome the harmful effect on morphological traits induced by different abiotic stress e.g., low moisture level (El-Samnoudi et al, 2019), salinity (Oustani et al, 2015;Rasool et al, 2023) The maximum field capacity creates a suitable environment for proper plant development and water stress reduces branch number. El-Samnoudi et al ( 2019) also found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Various research has established that water stress causes a decrease in growth, as seen by changes in plant growth parameters such as height, number of branches, and dry matter (Zubaer et al, 2007, Boutraa et al, 2010Talukdar, 2013). Poultry manure can overcome the harmful effect on morphological traits induced by different abiotic stress e.g., low moisture level (El-Samnoudi et al, 2019), salinity (Oustani et al, 2015;Rasool et al, 2023) The maximum field capacity creates a suitable environment for proper plant development and water stress reduces branch number. El-Samnoudi et al ( 2019) also found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in climate conditions are the main source of abiotic stresses, , which have adverse effects on agricultural lands . Such changes in climatic conditions are interlinked with each other in various aspects that negatively affect plant physiology. , The studies presented here were focused on the mitigating effects of woody biochar of V. nilotica L. and GA on morpho-anatomical, physiological, and biochemical aspects of S.…”
Section: Discussionmentioning
confidence: 99%
“… 91 Such changes in climatic conditions are interlinked with each other in various aspects that negatively affect plant physiology. 92 , 93 The studies presented here were focused on the mitigating effects of woody biochar of V. nilotica L. and GA on morpho-anatomical, physiological, and biochemical aspects of S. melongena L. under induced salinity and boron stress. Biochar is generally a carbon-rich compound that resists decomposition when applied to soil and increases EC, pH, and crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…portulacastrum in the present study interacted with the various physiological characteristics of wheat in a less damaging manner than synthetic herbicides. Chlorophyll has an imperative role in photosynthesis and represents a key indicator for tolerance investigation against stress. Mabasa et al described the depletion of chlorophyll content in two species of bean under plant extract and herbicide treatments. Water extracts of T.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll has an imperative role in photosynthesis and represents a key indicator for tolerance investigation against stress. 53 58 Mabasa et al 59 described the depletion of chlorophyll content in two species of bean under plant extract and herbicide treatments. Water extracts of T. portulacastrum reduced the levels of chlorophylls a and b in weed species.…”
Section: Discussionmentioning
confidence: 99%